Pengembangan Umkm Berbasis Digital Pasca Pandemi Covid-19 - Antony Antony (PT. Alahyan Publisher Sukabumi, 2023)
Thematic KKN activities carried out by Muhammadiyah Students of Sukabumi City are experiential learning activities, applications, and development of science and technology outside the campus environment involving the local government, the community, and the private sector. This Thematic KKN aims to solve problems faced by the local community, it is hoped that students can help overcome these problems and achieve targets related to existing problems. The COVID-19 pandemic has encouraged the development of digital-based MSMEs as a way to survive and grow amid a crisis. MSMEs that can adapt quickly to this digital era have a greater chance of success. Some of the advantages of digital-based MSMEs include wider market access, lower costs to market products, the ability to interact with customers online, and the ability to improve operational efficiency. Therefore, there needs to support government and related institutions to facilitate the development of digital-based MSMEs, including the provision of wider internet access and training and mentoring programs for business actors. In this case, the development of digital-based MSMEs has the potential to improve the skills and capacity of entrepreneurs and employees in using technology, marketing, and business management digitally. This will increase competitiveness and enable MSMEs to adapt to technological changes and ever-changing markets.